Effect of interstimulus interval on cortical proprioceptive responses to passive finger movements. (21st November 2016) - Smeds, Eero; Piitulainen, Harri; Bourguignon, Mathieu; Jousmäki, Veikko; Hari, Riitta
Abstract: Shortening of the interstimulus interval (ISI) generally leads to attenuation of cortical sensory responses. For proprioception, however, this ISI effect is still poorly known. Our aim was to characterize the ISI dependence of movement‐evoked proprioceptive cortical responses and to find the optimum ISI for proprioceptive stimulation. We measured, from 15 healthy adults, magnetoencephalographic responses to passive flexion and extension movements of the right index finger. The movements were generated by a movement actuator at fixed ISIs of 0.5, 1, 2, 4, 8, and 16 s, in separate blocks. The responses peaked at ~ 70 ms (extension) and ~ 90 ms (flexion) in the contralateral primary somatosensory cortex. The strength of the cortical source increased with the ISI, plateauing at the 8‐s ISI. Modeling the ISI dependence with an exponential saturation function revealed response lifetimes of 1.3 s (extension) and 2.2 s (flexion), implying that the maximum signal‐to‐noise ratio (SNR) in a given measurement time is achieved with ISIs of 1.7 s and 2.8 s respectively. We conclude that ISIs of 1.5–3 s should be used to maximize SNR in recordings of proprioceptive cortical responses to passive finger movements. Our findings can benefit the assessment of proprioceptive afference in both clinical and research settings. Abstract : We explored with MEG the effect of interstimulus interval (ISI) on proprioceptive SI‐cortex responses elicited by passive finger movements. Response strength (A) followed an exponential saturation function of ISI with response lifetimes of 1.3 s for extensions and 2.2 s for flexions. Our model indicated that an ISI of 1.5–3 s will maximize the responses' signal‐to‐noise ratio in a given recording time. The results help optimize assessment of proprioceptive afference both in health and disease.